Changes in the functional state of athletes under the influence of physical load - Baghirova, Rafiga (Edelweiss Applied Science and Technology, 2024)
The main goal of the presented research is to study the effect of sports physical activity on the quality of regulation and adaptive capacity of the cardiovascular system of athletes and non-athletes. The obtained results showed that the number of heart beats decreases during the rest period. Changes in the number of heart rates when performing a physical load correspond to the age norms of athletes. In addition, no significant changes were founding in the number of heart rates and systolic blood pressure, but diastolic blood pressure significantly decreased, and pulse pressure increased.